Diversidade sexual, proteção constitucional e controle de convencionalidade - Sales, Dimitri Nascimento (2014)
Body, sexuality and Law are elements that conform the subject. In society, body and sexuality are submitted to external means of control, that intends to control individuals. Law is the instrument through which behavioral patterns are imposed, limiting the fruition of corporal and sexual experimentations. To acknowledge sexual differences, whether centered in sexual orientation or gender identity, is to deny lesbians, gays, bisexuals, travesties and transsexuals the fulfillment of fundamental rights. This thesis analyses social interactions concerning sexuality, from a perspective that considers the relationship among body, sexuality and Law, stressing the means of control over the individual. Moreover, it will be studied the constitutional norms that protects the rights of sexual diversity. At the end, we scrutinize how the conventionality review has reshaped Brazilian constitutionalism and has impacted on the protection of lesbians, gays, bisexuals, travesties and transsexuals rights. The result of such study rests in the assurance that the rights of sexual diversity are inserted in the constitutional dimension, entailing the obligation to be enforced whether through the interpretation of the Constitution or through the interaction between constitutional law and international human rights, due to the conventionality review